The effect of a proposed training program to rehabilitate cartilage injury among volleyball and basketball players in clubs in the Syrian Arab Republic - ضعون مأمون; رشا ضويا (Latakia University Journal -Medical Sciences Series, 2024)
The study aimed to determine the extent of the effect of a group of therapeutic exercises to rehabilitate cartilage injuries in the knee joint on the severity of pain among a sample of (7) volleyball and basketball players in some first and second division clubs in the Syrian Arab Republic. The program was applied for a period of (12) weeks, and the study concluded that the program had a positive effect in improving the severity of pain in the cartilage of the knee joint.